2022
DOI: 10.1371/journal.ppat.1010327
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni infection induces plasmablast and plasma cell death in the bone marrow and accelerates the decline of host vaccine responses

Abstract: Schistosomiasis is a potentially lethal parasitic disease that profoundly impacts systemic immune function in chronically infected hosts through mechanisms that remain unknown. Given the immunoregulatory dysregulation experienced in infected individuals, this study examined the impact of chronic schistosomiasis on the sustainability of vaccine-induced immunity in both children living in endemic areas and experimental infections in mice. Data show that chronic Schistosoma mansoni infection impaired the persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…In the myeloid lineage, infection preferentially increased the frequency of bone marrow monocytes and eosinophils but not neutrophils or dendritic cells (Figure 1J-M). Infection significantly decreased bone marrow B cell frequency (Figure 1N) in agreement with a recent report (33). The infected spleen had an increased frequency and number of most myeloid lineage cell types (supplemental Figure 1Q-AB).…”
Section: Resultssupporting
confidence: 92%
“…In the myeloid lineage, infection preferentially increased the frequency of bone marrow monocytes and eosinophils but not neutrophils or dendritic cells (Figure 1J-M). Infection significantly decreased bone marrow B cell frequency (Figure 1N) in agreement with a recent report (33). The infected spleen had an increased frequency and number of most myeloid lineage cell types (supplemental Figure 1Q-AB).…”
Section: Resultssupporting
confidence: 92%
“…al. recently reported that lower responders to HepB vaccination had lower frequencies of cTfh cells and antibody-secreting plasmablasts (42); and Musaigwa and colleagues describe that S. mansoni infection specifically induces cell death in bone marrow plasmablasts and plasma cells (60). We show in addition to a lower frequency of cTfh cells in individuals with high CAA, a significant increase in activated B cells but a reduction in proliferating (antigen-specific) ASCs, ASCs expressing IgG and IgA, and that IgA + ASCs positively correlate with HepB titers.…”
Section: Discussionmentioning
confidence: 99%
“…The observation was further supported by Musaigwa et al (2022) that Sch. m infection affects vaccine response again TB infection by inducing deaths of plasmablast and plasma cells in the bone marrow [43].…”
Section: Schistosoma Mansoni Impairs Immune Response To Mycobacterium...mentioning
confidence: 99%